2012
DOI: 10.18406/2316-1817v4n12012369
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação dos depósitos da pulverização em frutos de cafeeiro utilizando dois equipamentos associados a diferentes volumes de calda

Abstract: Avaliação dos depósitos da pulverização em frutos de cafeeiro utilizando dois equipamentos associados a diferentes volumes de calda MIRANDA, Gustavo Rabelo Botrel et al. Avaliação dos depósitos da pulverização em frutos de cafeeiro utilizando dois equipamentos associados a diferentes volumes de calda.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 3 publications
2
14
0
2
Order By: Relevance
“…As in the present study, other authors have confirmed that in arboreal crops, good spray deposition is easier to achieve when the foliage has greater exposure to the spray nozzles (SCUDELER et al, 2004;RAMOS et al, 2007;FERNANDES et al, 2010;MIRANDA et al, 2012). The nozzles are closer to the lower part of the plant, which justifies the obtained results.…”
Section: Resultssupporting
confidence: 89%
“…As in the present study, other authors have confirmed that in arboreal crops, good spray deposition is easier to achieve when the foliage has greater exposure to the spray nozzles (SCUDELER et al, 2004;RAMOS et al, 2007;FERNANDES et al, 2010;MIRANDA et al, 2012). The nozzles are closer to the lower part of the plant, which justifies the obtained results.…”
Section: Resultssupporting
confidence: 89%
“…Dentro de cada grupo em estudo, pulverização com e sem assistência eletrostática, os diferentes volumes de calda não apresentaram significância, mostrando assim que é possível utilizar os menores volumes dentro de cada grupo, sem prejudicar a quantidade e distribuição de depósitos nas folhas do cafeeiro. Este resultado corrobora com os dados obtidos por Miranda et al (2012) e Ferreira et al (2013), que nos volumes de calda de 450 e 750 L ha -1 obtiveram depósitos equivalentes.…”
Section: Resultsunclassified
“…transformed. Miranda et al (2012) also compared pneumatic and hydraulic sprayers at different volumes on coffee plants and observed that applications with the hydraulic sprayer resulted in higher deposits on the lower parts of the plants. In addition, the application with the pneumatic sprayer was more homogeneous, contributing to a higher quality of application.…”
Section: Assessment Of Spray Deposition and Coverage -Experimentsmentioning
confidence: 99%